Spontaneous Contractions Evoke Afferent Nerve Firing in Mouse Bladders With Detrusor Overactivity - McCarthy, Carly J. (2009)
PURPOSE: Afferent nerve firing has been linked to spontaneous bladder contractions in a number of lower urinary tract pathologies and it may lead to urgency and incontinence. Using optical mapping, single unit recording and tension measurements we investigated the correlation between afferent nerve firing and spontaneous bladder contractions in spinal cord transected mice. MATERIALS AND METHODS: Bladder-nerve preparations (bladder sheets and the associated L6-S2 pelvic nerves) were dissected from normal and spinal cord transected mice showing overactivity on cystometry and opened along the ventral aspect from base to dome. Bladder sheets were mounted horizontally in a temperature regulated chamber to simultaneously record Ca(2+) transients across the mucosal surface, single unit afferent nerve firing and whole bladder tension. RESULTS: Single unit afferent fibers were identified by probing their receptive fields. Fibers showed a graded response to von Frey stimulation and a frequency of afferent firing that increased as a function of the degree of stretch. Optical maps of Ca(2+) transients in control bladders demonstrated multiple initiation sites that resulted in high frequency, low amplitude spontaneous contractions. Alternatively in maps of the bladders of spinal cord transected mice Ca(2+) transients arose from 1 or 2 focal sites, resulting in low frequency, high amplitude contractions and concomitant afferent firing. CONCLUSIONS: Large amplitude, spontaneous bladder contractions evoke afferent nerve activity, which may contribute to incontinence.